EFFECT OF TUBE CURRENT AND SLICE THICKNESS ON CT SCAN IMAGE QUALITY ON AAPM CT PERFORMANCE PHANTOM - Azzahra, Nazliah
An analysis of the effect of tube current and slice thickness on CT scan image quality has been conducted. This study aims to see the effect of each imaging parameter on the CT number and image quality produced by the AAPM CT Performance Phantom. This research focused on the CT number linearity insert of the phantom. The tube current ranged from 50 mA to 250 mA and and the slice thickness ranged from 1 mm to 8 mm. The CT scan image data consisting of five different materials was obtained. Furthermore, data processing is carried out. The data processing is done with ImageJ and Microsoft Excel. The amount of noise, contrast, and blurring from the image were analyzed. The accuracy and linearity of the resulting CT numbers were also analyzed. Noise and contrast were analyzed using a circular ROI placed on each material. While blurring is analyzed using line ROI placed vertically on each material. The noise value is obtained from the standard deviation of the CT number on the ROI. Contrast is calculated using the signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR). Blurring is obtained from the measurement of the penumbra width of the image profile curve. In this study, there is a difference between the measurement and reference CT numbers ranging from 4.58 HU to 11.5 HU. The linearity coefficient values obtained ranged from 0.980 to 0.983. The linearity coefficient value obtained illustrates that the CT scan machine used is able to produce images that match the density value of the material being imaged. The noise in the image is reduced by up to 29.3% when the tube current is increased. Meanwhile, when the slice thickness is increased, the noise is reduced by 22.8%. The SNR and CNR values increase as the tube current and slice thickness are increased. When the tube current is increased, the SNR and CNR increase by 21.8% and 20.5%, respectively. When the slice thickness was increased, the SNR and CNR increased by 21.08% and 20.4%, respectively. The blurring value of the penumbra width is increased by 25% as the slice thickness is increased. While the increase in tube current does not have an impact on the blurring.